ANALYSIS OF THE IMPACT OF THE EXTENSION OF CREDIT RESTRUCTURING ON BANKING SOUNDNESS - Syahputra, Ari; Suwadi, Suwadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this research is to analyze the impact of the extention credit restructuring on banking soundness. This research uses a quantitative approach, where the data used is secondary data. Secondary data is obtained by using documentation techniques. The population in this research were Regional Development Banks registered with the OJK until 2019 as many as 25 banks, all of which were used as samples or with saturated sampling technique. Hypothesis testing using independent sample t-test. The results of the research show that there are differences in the Loan to Deposit Ratio (LDR), Return On Assets (ROA) and Capital Adequacy Ratio (CAR) between before and after the extension of credit restructuring, while in Non Performing Loans (NPL), Net Interest Margin (NIM) and Good Corporate Governance (GCG) there is no difference between before and after the extension of credit restructuring. Overall assessment using a composite rating of bank soundness there is no difference between before and after the extension of credit restructuring, namely banking soundness is at composite rating 2 with a healthy predicate.